THE EPISOOTOLOGICAL FEATURES OF SARCOPTOSIS DOGS IN POLTAVA - Kravchenko, S. O.; Melnychuk, V. V.; Kanivets, N. S.; Burda, T. L. (Scientific Progress & Innovations, 2020)
Diseases, caused by Acariformes have become a serious problem for owners of domestic animals, including dogs. Sarcoptic scab is one of such diseases caused by Sarcoptes scabiei var. canis, Gerlach, 1857 sarcoptiform mites. Despite a considerable number of available medicaments on the market of veterinary preparations used to fight sarcoptic invasion, the amount of diseased animals gradually increases, which indicates the topicality of studying separate aspects connected with spreading the invasion on certain territories. The aim of the article was to determine the level of infestation with dog sarcoptic scab in the city of Poltava. The studies were conducted in the laboratory of parasitology at the Department of Parasitology and Veterinary- Sanitary Expert Examination and at the clinic of veterinary medicine “Lokes-Krupka T.P.” at the Department of Therapy named after P. I. Lokes at Poltava State Agrarian Academy. In order to diagnose the disease, acarological studies of dogs using the method of V. O. Yevstafieva and others were applied. According to this method, the mixture of “Bischofite” and glycerin, one part to one, was used for softening and clearing scrapings from the skin; the scrapings were kept in the mixture for 1-2 minutes. In all, 11 dogs of different breeds (decorative, utility, hunting), as well as mongrels and non-pedigree animals were studied; dogs were distributed in four age groups: young animals up to 1 year old, dogs from 1 to 4 years old, from 4 to 8 years old and those older than 8. As a result of acarological studies, it has been revealed that dogs are infected with sarcoptic scab on the territory of Poltava. The infestation index made 18.20 %, on the average. It should be mentioned that dog sarcoptic invasion had certain peculiarities. It has been found that animals of various breeds were infected with sarcoptic scab causative agent differently. Animals of hunting breeds, non-pedigree, and mongrels were affected most of all (EI=38.46 and 36.76 %, respectively). Dogs of decorative breeds were the least infected (ЕІ=3.92 %). Besides, the infestation index of dogs also depended on their age. It has been revealed that dogs aged from 1 to 4 years and from 4 to 8 years turned out to be infected with the causative agent of sarcoptic scab most of all (ЕІ=45.81 and 42.94 %, respectively). Thus, the obtained data have significant scientific and practical importance, because they supplement the information concerning epizootic condition as to sarcoptic invasion of dogs in the city of Poltava.